GAMBARAN HEMODINAMIK PASIEN SAAT PEMASANGAN BONE CEMENT AMP DENGAN ANESTESI REGIONAL : STUDI KASUS HEMODYNAMIC PICTURE OF PATIENTS DURING BONE CEMENT AMP INSTALLATION WITH REGIONAL ANESTHESIA: A CASE STUDY - Annisa Luthfiyyah Utami; Bulan Salsabila Putri; Maria Natalia Putri Hapsari; Shinta Rambu Atanyungga Taralandu; Taqiyah Kamila Az Zahra; Ganik Sakitri (STKIP Subang, 2026)
Bone cement placement in Austin Moore Prosthesis (AMP) procedures has the potential to cause significant hemodynamic changes, especially due to the risk of Bone Cement Implantation Syndrome (BCIS). On the other hand, the use of regional anesthesia is known to affect the stability of the cardiovascular system through the mechanism of sympathetic blockade. This study aims to analyze the hemodynamic conditions of patients during bone cement placement in AMP procedures with regional anesthesia. This study used a descriptive observational design with a prospective approach. The study sample consisted of 5 respondents taken using a total sampling technique at Dr. Harjono S. Ponorogo Regional General Hospital in the period February-March 2026. The data collected included systolic, diastolic blood pressure, and pulse rate in the pre-, intra-, and post-bone cement placement phases. Data analysis was carried out descriptively using the average, minimum, maximum, and standard deviation values. The results showed that the patient's hemodynamic parameters were relatively stable throughout the observation phase. The average systolic blood pressure decreased slightly in the intraoperative phase but increased again in the postoperative phase. A similar pattern was also found in diastolic blood pressure and pulse rate, with minimal changes. All respondents (100%) were hemodynamically stable and did not require vasopressor intervention. This study demonstrates that the use of regional anesthesia for AMP bone cement placement can maintain patient hemodynamic stability. However, close hemodynamic monitoring is still necessary to anticipate potential intraoperative complications.